Kepemimpinan Perempuan (Studi kasus pada Program Studi Pendidikan Bahasa Inggris Institut Pendidikan Islam Garut) - Ima Rahmawati (Institut Agama Islam Sahid (INAIS) Bogor, 2019)
This study aims to analyze the factors of electing women to become chairmen of study programs, leadership styles, and the obstacles they face. This research uses a case study approach with qualitative methods. The data source is a head of the women's study program, six lecturers, and two employees. The triangulation technique was carried out to assess the validity of the data. Factors for the selection of female leaders in the English Language Education study program at the Islamic Education Institute (IPI) Garut are good character, support from various parties, competent and experienced, have a vision, and are selected through a formal decision. The leadership style applied is transformational. The obstacle faced is in encouraging lecturers to manage and fulfill the requirements of functional positions.